Holisme as "n postmodernistiese filosofie in teologiese lig - Aarde, Andries van (Hervormde teologiese studies, 1990)
Holism as a postmodern philosophy in theological light Postmodernity is defined primarily as advocacy for holistic thinking as against the alleged fragmentation in epistemology in the Modern Time. The aim of this article is to describe holism in terms of the modernity-postmodernity debate. It is approached from a theological perspective. Since the Kantian revolution in the Modern Time, metaphysical knowledge has been articulated by influential theologians in the language of analogy. It is shown here that holism as a postmodern philosophy is a departure from theology in the modern sense of the word and, as monistic-metaphysical thinking, it thus has serious consequences. However, holism should not be defined as a paradigm-shift in epistemology.